Differences in the neovascular potential of thymus versus subcutaneous adipose-derived stem cells from patients with myocardial ischaemia. - Oliva Olivera, Wilfredo; Coín-Aragüez, Leticia I.; Lhamyani, Said; Salas-Millán, Manuel Julián; Gentile, Adriana Mariel; Romero-Zerbo, Silvana Yanina; Zayed, Hatem; Valderrama-Marcos, José Francisco; Tinahones-Madueño, Francisco José; El-Bekay, Rajaa (Wiley, 2017)
Adipose tissue‐derived multipotent mesenchymal cells (ASCs) participate in the information ofblood vessels under hypoxic conditions. It is probable that the susceptibility of ASCs to theinfluence of age and ageing‐associated pathologies compromises their therapeutic effectivenessdepending on the adipose tissue depot. Our aim was to examine the neovascular potential underhypoxic conditions of ASCs‐derived from thymic (thymASCs) and subcutaneous (subASCs)adipose tissue from 39 subjects with and without type 2 diabetes mellitus (T2DM) and ofdifferent ages who were undergoing coronary bypass surgery. We confirmed a significant decreasein the percentage of CD34+CD31−CD45− subASCs in the cell yield of subASCs and in the survivalof cultured endothelial cells in the medium conditioned by the hypox‐subASCs with increasingpatient age, which was not observed in thymASCs. Whereas the length of the tubules generatedby hypox‐subASCs tended to correlate negatively with patient age, tubule formation capacity ofthe hypoxic thymASCs increased significantly. Compared with subASCs, thymASCs from subjectsover age 65 and without T2DM showed higher cell yield, tubule formation capacity, vascularendothelial growth factor secretion levels, and ability to promote endothelial cell survival in theirconditioned medium. Deterioration in subASCs neovascular potential relative to thymASCs derivedfrom these subjects was accompanied by higher expression levels of NOX4 mRNA and fibroticproteins. Our results indicate that thymASCs from patients over age 65 and without T2DM have ahigher angiogenic potential than those from the other patient groups, suggesting they may be a goodcandidate for angiogenic therapy in subjects undergoing coronary bypass surgery.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/7509
Keywords: Arterias coronarias - Enfermedades; Arteriosclerosis -Tratamiento; Cardiopathy ischaemia; Elderly; Multipotent mesenchymal cells; Neovascular; Thymus fat; Type 2 diabetes